Molecular, biochemical and anatomical analysis of some potato (Solanum tuberosum L.) cultivars growing in Egypt - H.A.M. Mahgoub; G.S.A. Eisa; M.A.H. Youssef (Journal of Genetic Engineering and Biotechnology, 2015)
Potato (Solanum tuberosum L.) is widely used for many industrial and food applications. Nine potato cultivars were planted and collected from a private farm in new Salihiyyah city, Sharkia governorate, Egypt to compare between them at morphological, molecular, biochemical and anatomical levels. Our results indicated that the Inova cultivar was better, however the Bafana cultivar was worse in relation to yield parameters. Inter simple sequence repeat (ISSR) molecular marker has been used to determine the genetic diversity between these nine cultivars. Through using ten primers we obtained 98 bands, 85 of which were polymorphic by 87%. The highest similarity value (0.827) was found between Caruso and Alliance as the closest but the lowest value (0.418) was found between Charlotte and Bafana as the most distant. Everest tuber contained great amounts of total phenolic and peroxidase activity, while the Bafana tuber contained small amounts of it compared to other cultivars. The phellem layer of the Everest tuber had more thickness than others and the number of phellem rows was the highest. However, the Bafana cultivar listed the lowest value compared to other cultivars. Lower values from both of total bacterial and total fungi were recorded on the tuber of the Everest cultivar. However, Bafana cultivar was recorded to have a higher value of both compared to other cultivars. We suggest that the ISSR marker is a suitable procedure to examine the potato’s genetic diversity at the DNA level. The Everest cultivar is considering the best cultivar to planting and breeding in Egypt.